2015
DOI: 10.1002/humu.22737
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RAS Activation Due to a Homozygous Ezrin Variant in Patients with Profound Intellectual Disability

Abstract: Gain-of-function alterations in several components and modulators of the Ras-MAPK pathway lead to dysregulation of the pathway and cause a broad spectrum of autosomal dominant developmental disorders, collectively known as RASopathies. These findings demonstrate the importance of tight multilevel Ras regulation to safeguard signaling output and prevent aberrant activity. We have recently identified ezrin as a novel regulatory element required for Ras activation. Homozygosity mapping and exome sequencing have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Of the targeted regions, 73.2% were covered at least 20×, and 83.4% were covered at least 5×. To validate the results, we also conducted WES in the likewise affected sibling, MR026-04, analogous to previously described disease gene identification approaches ( Ahmed et al, 2015 ; Riecken et al, 2015 ). 96% of the target sequence were covered at least 20×.…”
Section: Methodsmentioning
confidence: 87%
“…Of the targeted regions, 73.2% were covered at least 20×, and 83.4% were covered at least 5×. To validate the results, we also conducted WES in the likewise affected sibling, MR026-04, analogous to previously described disease gene identification approaches ( Ahmed et al, 2015 ; Riecken et al, 2015 ). 96% of the target sequence were covered at least 20×.…”
Section: Methodsmentioning
confidence: 87%
“…We have previously shown that ezrin is actively involved in Ras activation by directly binding to both Ras and Son of Sevenless (SOS), a major Ras GEF [15, 16]. The F1 subdomain of FERM is an ubiquitin/Raf1-RBD-like domain [17] and the F1–F2 subdomains of ezrin FERM appear to mediate Ras binding [15, 18], suggesting that merlin may do likewise. Indeed, merlin FERM (amino acids [aa] 1–313), but not the α-helical-tail domains (aa 312–595), could pull down purified HRas 1–166 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro functional studies of this missense allele demonstrated normal cell membrane localization compared to the wildtype protein when expressed in fibroblasts, but failure to bind RAS and thus activate the RAS pathway [Riecken et al, 2015]. NEC was not reported in these patients with EZR point mutations; however, it may be that amino acid substitutions are phenotypically different than whole gene deletions.…”
Section: Esdal Et Almentioning
confidence: 96%
“…A human phenotype associated with the EZR mutation was recently suggested by Riecken et al [2015] who reported 2 siblings with profound intellectual disability and homozygous mutations in EZR , p.Ala129Thr. In vitro functional studies of this missense allele demonstrated normal cell membrane localization compared to the wildtype protein when expressed in fibroblasts, but failure to bind RAS and thus activate the RAS pathway [Riecken et al, 2015].…”
Section: Esdal Et Almentioning
confidence: 99%